ESTADO NUTRICIONAL Y PRÁCTICAS ALIMENTICIAS EN GESTANTES ATENDIDAS EN EL CLAS CENTRO DE SALUD EL CARMEN PERIODO JULIO A DICIEMBRE DEL 2019 - ACCINELLI MONTERO, INGRID DAYANA (2020)
Objective: "Determine the nutritional status and feeding practices in pregnant women attended at the CLAS El Carmen Health Center from July to December 2019". Methodology and Technique: The study was a qualitative approach of basic design and correlational type, with a population of 65 pregnant women attended at the "CLAS Centro de Salud El Carmen". The data collection instrument that was applied was the data collection form, made up of 27 questions, structured in 3 sections. For data analysis, it was done using a descriptive and systematic statistical criterion. Results: It is evident that the sociodemographic characteristics of pregnant women, the average age is 15 to 25 years (57.8%), the marital status married (39.1%), the predominant occupation is a housewife (57.8%) ), regarding the predominant level of education is secondary (56.3%), the place of origin of the pregnant women is rural (51.6%), the average number of children is 1 child. The average BMI of gravid women is normal weight (51.6%), 40.6% have a “high” weight gain, the eating practices of gravid women are favorable in 78.1%, 21.9% is unfavorable. While eating practices are not related to weight gain (chi-square = 1,392) where 26 pregnant women present a "high" weight gain and have "adequate" eating practices; 3.7% with "low" weight gain have "inadequate" eating practices, 11 of the pregnant women with "adequate" weight gain have adequate eating practices, that pregnant women with anemia only 11 have "adequate" eating practice and 1 with “inadequate” eating practices, of the pregnant women without anemia 52 have “adequate” feeding practices. Conclusion: The feeding practices of the pregnant women attended at the "CLAS El Carmen Health Center" do not bear any relation to weight gain (Chi-square = 1,392). Key words: Nutrition, Pregnant, Physiological changes in pregnancy, Gestational Age, BMI.